One good knight - Lackey, Mercedes (New York, NY : Luna Books, 2006)
When George, the Good Knight, arrives to save Princess Andromeda from the dragon for whom she is to be a virgin sacrifice, he does not exactly defeat the dragon, and he and the princess must join forces to find the dragon's lair and destroy it.
Keywords: Dragons -- Fiction